Origins of the Chinese Revolution, 1915-1949. [Forew. by M. Selden]. Transl. from the French by M. Bell (Stanford University Press etc., 1972)
With bibliogr., index, maps and tab. Original title: "Les origines de la Révolution chinoise, 1915-1949"